Pengaruh Dosis Pemberian Enzim Bromelin Terhadap Ukuran Linear Tubuh Ayam Ipb-D1 Generasi Pertama - Yunus, Lidia Meilinda Arafah; Suryatni, Ni Putu Febri; Theedens, Jonas F. (Animal Agricultura, 2024)
This study aims to determine the effect of the dose of bromelain enzyme on the linear body size of first generation IPB-D1 chickens. The livestock used were 80 first generation IPB-D1 chickens aged 4 weeks. This research method used a Completely Randomized Design consisting of 4 treatments and 5 replications. Each replication consisted of 4 chickens. The treatment given was E0 = Drinking water without enzyme (control), E1=4 ml of bromelain enzyme/liter of water, E2= 8 ml of bromelain enzyme/liter of water and E3=12 ml of bromelain enzyme/liter of water. The research variables included back length, chest circumference, wing span and shank length. The results of the study showed that the use of the bromelain enzyme had no significant effect (P>0.05) on back length, chest circumference, wing span and shank length at 4 weeks of age. 8 and 12 weeks. It was concluded that the use of the bromelain enzyme in drinking water up to a dose of 12 ml had the same effect on the linear body size of first generation IPB-D1 chickens.